2017
DOI: 10.1053/j.gastro.2017.02.006
|View full text |Cite|
|
Sign up to set email alerts
|

Solute Carrier Family 39 Member 6 Gene Promotes Aggressiveness of Esophageal Carcinoma Cells by Increasing Intracellular Levels of Zinc, Activating Phosphatidylinositol 3-Kinase Signaling, and Up-regulating Genes That Regulate Metastasis

Abstract: In an analysis of ESCC samples and cell lines, we associated increased expression of SLC39A6 with tumor invasiveness, intracellular level of zinc, and patient survival time. ESCC cell lines that overexpress SLC39A6 up-regulate expression MMP1, MMP3, MYC, and SLUG and form metastatic xenograft tumors in mice. Up-regulation of SLC39A6 might be used to determine prognoses of patients with ESCC or as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…The enzyme is also considered to be involved in wound repair, atherosclerosis progression and tumorigenesis [31]. In another study, the expressions of SLUG, MMP1, MMP3, and MYC were found to be correlated, suggesting that SLUG may play a role as a transcription factor for MMP1 and MMP3 [32]. Our gene microarray results showed that MMP1 and MMP3 were signi cantly upregulated in SLUG overexpressing cells, which was further con rmed by quantitative PCR and western blot.…”
Section: Discussionsupporting
confidence: 69%
“…The enzyme is also considered to be involved in wound repair, atherosclerosis progression and tumorigenesis [31]. In another study, the expressions of SLUG, MMP1, MMP3, and MYC were found to be correlated, suggesting that SLUG may play a role as a transcription factor for MMP1 and MMP3 [32]. Our gene microarray results showed that MMP1 and MMP3 were signi cantly upregulated in SLUG overexpressing cells, which was further con rmed by quantitative PCR and western blot.…”
Section: Discussionsupporting
confidence: 69%
“…And slug, together with MMP2, MMP9 and c-Myc, have been well characterized as downstream targets of AKT and ERK. [23][24][25][26] Ewald et al said that COL11A1 may promote bladder cancer invasiveness through PI3K/Akt and Ras/ERK signaling pathway. 27 Wu et al highlighted the magnitude of COL11A1 in chemoresistance of ovarian cancer patients through increasing p-AKT expression; comparing to chemo-naive cells, chemoresistant cells exhibited stronger intensity and higher proportion of COL11A1 staining among positive cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu et al found that amplification of SLC12A5 plays a strong tumorigenic role and is associated with poor prognosis of patients with colorectal cancer . SLC39A6 promotes aggressiveness of esophageal squamous carcinoma cells by increasing intracellular levels of zinc and activates phosphatidylinositol 3‐kinase (PI3K) pathway . SLC35, a group of nucleotide sugar transporters, currently comprises at least 31 homologous molecular species from SLC35A to SLC35G.…”
Section: Introductionmentioning
confidence: 99%
“…6 SLC39A6 promotes aggressiveness of esophageal squamous carcinoma cells by increasing intracellular levels of zinc and activates phosphatidylinositol 3-kinase (PI3K) pathway. 7 SLC35, a group of nucleotide sugar transporters, currently comprises at least 31 homologous molecular species from SLC35A to SLC35G. SLC35A2 functions as a UDP-galactose transporter, whose substrate is required for galactosylation.…”
Section: Introductionmentioning
confidence: 99%